2006
DOI: 10.1111/j.1469-8137.2006.01888.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium–calmodulin is required for abscisic acid‐induced antioxidant defense and functions both upstream and downstream of H2O2 production in leaves of maize (Zea mays) plants

Abstract: Summary• Using pharmacological and biochemical approaches, the role of calmodulin (CaM) and the relationship between CaM and hydrogen peroxide (H 2 O 2 ) in abscisic acid (ABA)-induced antioxidant defense in leaves of maize ( Zea mays ) plants were investigated.• Treatment with ABA or H 2 O 2 led to significant increases in the concentration of cytosolic Ca 2 + in the protoplasts of mesophyll cells and in the expression of the calmodulin 1 ( CaM1 ) gene and the content of CaM in leaves of maize plants, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
123
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(131 citation statements)
references
References 46 publications
4
123
1
3
Order By: Relevance
“…Regardless of the absolute amount of ABA, the slope shift observed at 6 dS m -1 for both ecotypes versus salinity is noticeable and this was more pronounced in Siyah Shiraz ecotype than Sefid Shiraz one. These results are consistent with those of Yang et al (2014) and Lovelli et al (2012) in tomato (Solanum lycopersicum) and Hu et al (2006) in maize (Zea mays), who reported that salt tolerant plants contain more ABA concentration than sensitive ones. In addition, ABA activates the expression of genes encoding antioxidant enzymes, increasing the activity of antioxidant enzymes including superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX) (Yang et al, 2014).…”
Section: Abscisic Acidsupporting
confidence: 91%
See 2 more Smart Citations
“…Regardless of the absolute amount of ABA, the slope shift observed at 6 dS m -1 for both ecotypes versus salinity is noticeable and this was more pronounced in Siyah Shiraz ecotype than Sefid Shiraz one. These results are consistent with those of Yang et al (2014) and Lovelli et al (2012) in tomato (Solanum lycopersicum) and Hu et al (2006) in maize (Zea mays), who reported that salt tolerant plants contain more ABA concentration than sensitive ones. In addition, ABA activates the expression of genes encoding antioxidant enzymes, increasing the activity of antioxidant enzymes including superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX) (Yang et al, 2014).…”
Section: Abscisic Acidsupporting
confidence: 91%
“…Under salt stress, ABA levels increased dramatically with increased salinity in chicory ecotypes leaves (Figure 4), suggesting that ABA acts as a signal in salt response. ABA controls many stress adaptation responses, including stomatal closure, activation of genes involved in osmotic adjustment, ion compartimentation, regulation of shoot versus root growth and modifications of root hydraulic conductivity properties (Jiang et al, 2002;Zhang et al, 2006;Hu et al, 2006;Antoni et al, 2011;Javid et al, 2011). Regardless of the absolute amount of ABA, the slope shift observed at 6 dS m -1 for both ecotypes versus salinity is noticeable and this was more pronounced in Siyah Shiraz ecotype than Sefid Shiraz one.…”
Section: Abscisic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence indicates that ABAenhanced water stress tolerance is, at least in part, due to the induction of antioxidant defense systems [3][4][5][6]. Previous studies have shown that NADPH oxidase, hydrogen peroxide (H 2 O 2 ), nitric oxide (NO), calcium (Ca 2+ )-calmodulin (CaM), and mitogen-activated protein kinase (MAPK) are required for ABA-induced up-regulation in the activities of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX) and glutathione reductase (GR) in leaves of maize plants [7][8][9][10][11]. It has been shown that ABA-induced H 2 O 2 production mediates NO generation, which, in turn, activates MAPK and results in the up-regulation in the expression and the activities of antioxidant enzymes in ABA signaling [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ABA-induced H 2 O 2 production mediates NO generation, which, in turn, activates MAPK and results in the up-regulation in the expression and the activities of antioxidant enzymes in ABA signaling [11]. Ca 2+ -CaM has also been shown to be necessary for ABAinduced antioxidant defense and function both upstream and downstream of H 2 O 2 production in leaves of maize plants [9]. However, whether Ca 2+ -CaM is involved in NO-induced antioxidant defense in plants and, if so, what the relationship between Ca 2+ -CaM and NO in the ABA signaling is remains to be determined.…”
Section: Introductionmentioning
confidence: 99%